Gender, population and development - Krishnaraj Maithreyi; Shariff Abusaleh; Sudarshan Ratna M (Oxford OUP, 2002)
The papers in this volume link gender with development through two distinct sets of conditions: individual endowments and structural constraints for gender equity. They examine the basis of gender discrimination and the policy perspectives rising therefr
Keywords: Birth control; India; Population policy; Social conditions; Women; Women in development